Carbon material and method for producing the same

A carbon material with controlled pores and enhanced mechanical strength is achieved by forming openings in a carbon-containing layer using a metal complex, addressing the challenges of crack formation and drilling uniformity in graphene-like materials.

JP7607270B2Active Publication Date: 2024-12-27TAKAGI CO LTD +1
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2022504358
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-03-05
Filing Date
2021-03-01
Publication Date
2024-12-27
Estimated Expiration
2041-03-01

AI Technical Summary

Technical Problem

Graphene and similar materials face challenges in controlled drilling due to their uniform chemical environment and hexagonal lattice structure, leading to potential cracks and difficulty in suppressing their spread.

Method used

A carbon material with a carbon-containing layer having openings covered by a solid substance, where the solid substance has a hole communicating with the opening, is produced by attaching a metal complex to the carbon-containing layer, forming an opening, and removing metal atoms to create pores, thereby suppressing crack spread and enhancing mechanical strength.

Benefits of technology

The method results in a carbon material with controlled pores and excellent mechanical strength, allowing for easier control of opening diameter and reducing crack formation during the drilling process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007607270000005
    Figure 0007607270000005
  • Figure 0007607270000006
    Figure 0007607270000006
  • Figure 0007607270000007
    Figure 0007607270000007
Patent Text Reader

Abstract

One aspect of the present disclosure provides a carbon material including: a carbon-containing layer having an opening; and a solid material provided so as to cover the opening of the carbon-containing layer, wherein the solid material has a hole section communicating with the opening.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to carbon materials and methods for making carbon materials. [Background technology]

[0002] Graphene, carbon nanotubes, carbon nanohorns, etc. are expected to be used in various applications due to their mechanical and electrical properties. For example, research is being conducted to form fine water-permeable pores in graphene and use it as a filter for desalting or deionizing solutions, and research is being conducted to form fine pores in carbon nanotubes and carbon nanohorns and use them as molecular sieves for gas separation.

[0003] Patent Document 1 describes a method for perforating graphene, comprising the steps of exposing a gas flow to atmospheric pressure plasma and generating an activated gas flow separated from the atmospheric pressure plasma downstream of the atmospheric pressure plasma, directing the activated gas flow separated from the atmospheric pressure plasma toward a graphene sheet, and perforating the graphene sheet with the activated gas flow, wherein the gas flow has a certain concentration of activated gas, and the activated gas is selected from one of oxygen, nitrogen, or a combination thereof.

[0004] Patent Document 2 describes a method for perforating a sheet of a graphene-based material, the method including positioning a sheet of the graphene-based material including a single-layer graphene having at least two surfaces, and a non-graphene carbon-based material formed on the single-layer graphene, and covering more than 10% and less than 80% of the surface of the single-layer graphene with the non-graphene carbon-based material, and perforating the sheet of the graphene-based material with an ion energy of 10 eV to 100 keV and 1×10 13 ions / cm 2 ~1×10 21 ions / cm 2 The method comprises exposing the substrate to ions characterized by a fluence having a magnitude of: [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Special Publication No. 2013-536077 [Patent Document 2] Special Publication No. 2018-529612 Summary of the Invention [Problem to be solved by the invention]

[0006] However, graphene and the like have a hexagonal lattice structure composed of multiple carbon atoms as a basic structure, and the chemical environment on the surface is uniform. This can make it difficult to control the drilling of holes. In addition, in conventional drilling techniques for graphene and the like, cracks can occur in the graphene during or after drilling, and it can be difficult to suppress the spread of the cracks.

[0007] The present disclosure has an object to provide a carbon material having pores and excellent mechanical strength in which cracks are suppressed from spreading, etc. The present disclosure also has an object to provide a method for producing the above-mentioned carbon material. [Means for solving the problem]

[0008] One aspect of the present disclosure provides a carbon material including: a carbon-containing layer having an opening; and a solid body provided so as to cover the opening of the carbon-containing layer, the solid body having a hole portion communicating with the opening.

[0009] The carbon material has openings that the carbon-containing layer has, and a solid material is provided on the openings, which suppresses the spread of cracks and provides excellent mechanical strength.

[0010] The carbon-containing layer may be a monolayer.

[0011] The carbon-containing layer may contain at least one selected from the group consisting of graphene and graphene oxide.

[0012] The solid may contain at least one selected from the group consisting of phthalocyanine, porphine, porphyrin, corrole, chlorine, and derivatives thereof.

[0013] A plurality of the solid objects may be arranged on the carbon-containing layer.

[0014] A plurality of the solid objects may be regularly arranged on the carbon-containing layer.

[0015] One aspect of the present disclosure provides a method for producing a carbon material, the method including: a first step of reducing a content of the solvent from a dispersion containing a carbon-containing layer, a metal complex, and a solvent to form a composite in which the metal complex is attached to a surface of the carbon-containing layer; a second step of heat-treating the composite to provide openings in the carbon-containing layer near metal atoms constituting the metal complex; and a third step of removing at least a portion of the metal atoms constituting the metal complex to form a solid material having pores communicating with the openings.

[0016] The method for producing the carbon material includes a step of adhering a metal complex to a carbon-containing layer and forming an opening by utilizing a metal element of the metal complex. Therefore, the opening can be formed under relatively mild conditions, and a carbon material having excellent mechanical strength and in which the spread of cracks is suppressed can be provided.

[0017] The heating temperature in the second step may be 200 to 450° C. By setting the heating temperature in the second step within the above range, it becomes easier to control the opening diameter of the opening, and the occurrence of cracks can be more sufficiently suppressed.

[0018] The second step may be a step of providing openings in the carbon-containing layer near metal atoms constituting the metal complex by causing the complex to coexist with ammonium nitrate and heat-treating it at 200 to 280° C. under vacuum.

[0019] The third step may be a step of removing at least a part of the metal atoms by acid treatment. By carrying out the third step by acid treatment, the removal of the metal atoms and the formation of the pores become easier.

[0020] The metal atoms may include at least one selected from the group consisting of transition metals, alkaline earth metals, and aluminum. When the metal atoms include at least one selected from the group consisting of the above-mentioned metal atoms, it becomes easier to provide openings in the carbon-containing layer.

[0021] The transition metal may include at least one metal atom selected from the group consisting of iron, copper, cobalt, vanadium, nickel, aluminum, zinc, alkaline earth metals, and lanthanoids. When the metal atom includes at least one metal atom selected from the above-mentioned metal atoms, it becomes easier to provide openings in the carbon-containing layer.

[0022] The carbon-containing layer may be a monolayer.

[0023] The carbon-containing layer may contain at least one selected from the group consisting of graphene and graphene oxide.

[0024] The metal complex may include a complex of at least one selected from phthalocyanine, porphine, porphyrin, corrole, chlorine, and derivatives thereof with a metal atom. By including a complex of the phthalocyanine or the like with a metal atom in the metal complex, it becomes easy to arrange the metal complex with a certain regularity on the carbon-containing layer.

[0025] A plurality of the solid objects may be arranged on the carbon-containing layer.

[0026] A plurality of the solid objects may be regularly arranged on the carbon-containing layer. Effect of the Invention

[0027] According to the present disclosure, it is possible to provide a carbon material having pores and excellent mechanical strength in which cracks are suppressed from spreading, etc. According to the present disclosure, it is also possible to provide a manufacturing method for manufacturing the above-mentioned carbon material. [Brief description of the drawings]

[0028] [Figure 1] FIG. 1 is a schematic cross-sectional view showing an example of a carbon material. [Diagram 2] FIG. 2 is a graph showing the ultraviolet-visible absorption spectrum of the carbon material prepared in Example 1. [Diagram 3] FIG. 3 is a graph showing the ultraviolet-visible absorption spectrum of the carbon material prepared in Example 2. [Figure 4] FIG. 4 is a graph showing the results of thermogravimetry of a carbon material in an oxygen atmosphere. [Diagram 5] FIG. 5 is a graph showing the results of thermogravimetry of a carbon material in a nitrogen atmosphere. [Figure 6] FIG. 6 is a graph showing the relationship between the nitrogen adsorption amount of the carbon material and the relative nitrogen pressure. [Figure 7] FIG. 7 is a graph showing the relationship between the amount of argon adsorption per pore volume determined by nitrogen adsorption of a carbon material and the argon pressure. [Figure 8] FIG. 8 is a graph showing the relationship between the amount of sulfur hexafluoride adsorbed per pore volume determined by nitrogen adsorption of a carbon material and the pressure of sulfur hexafluoride gas. [Figure 9] FIG. 9 is an electron microscope image of the sheet surface during the production process of the carbon material in Example 4. [Figure 10] FIG. 10 is an electron microscope image of the sheet surface in the manufacturing process of the carbon material in Comparative Example 3. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0029] Hereinafter, embodiments of the present disclosure will be described with reference to the drawings in some cases. However, the following embodiments are merely examples for explaining the present disclosure, and are not intended to limit the present disclosure to the following contents. Positional relationships such as up, down, left, and right are based on the positional relationships shown in the drawings unless otherwise specified. The dimensional ratios of each element are not limited to the ratios shown in the drawings.

[0030] Unless otherwise specified, the materials exemplified in this specification can be used alone or in combination of two or more. When a plurality of substances corresponding to each component are present in the composition, the content of each component in the composition means the total amount of the plurality of substances present in the composition, unless otherwise specified.

[0031] One embodiment of the carbon material includes a carbon-containing layer having an opening, and a solid body provided so as to cover the opening of the carbon-containing layer. The solid body has a hole portion that communicates with the opening. The form of the carbon material may be, for example, a film or a cylinder. The end of the cylinder may be in an open state or in a closed state. When the end of the cylinder is in an equilibrium state, the end may be composed of the same elements as the carbon-containing layer. The aggregate of the carbon material may be, for example, in a powder form.

[0032] FIG. 1 is a schematic cross-sectional view showing an example of a carbon material. The carbon material 10 has a carbon-containing layer 2 and a solid material 4. The carbon-containing layer 2 has a plurality of openings 2a, and the solid material 4 is provided so as to cover the openings 2a. The solid material 4 is provided on the openings 2a of the carbon-containing layer 2, but since the solid material 4 also has holes 4a, the carbon material 10 has through holes consisting of the openings 2a of the carbon-containing layer 2 and the holes 4a of the solid material 3. The opening diameter of the openings 2a is usually larger than the opening diameter of the holes 4a. The openings 2a and the holes 4a refer to regions in which the elements constituting the carbon-containing layer 2 and the elements constituting the solid material 4 are absent, respectively. Although only a partial cross-section is shown in FIG. 1, the openings 2a may be present in a plurality of locations spreading in the in-plane direction of the carbon-containing layer 2, and the plurality of openings 2a may be present regularly at a predetermined interval. Similarly, the solid material 4 may be present in a plurality of locations spreading in the in-plane direction on the carbon-containing layer 2, and may be present in a plurality of locations regularly arranged at a predetermined interval.

[0033] The carbon-containing layer 2 may be composed of, for example, a monolayer or may be composed of multiple layers. From the viewpoint of facilitating control of the openings 2a, the carbon-containing layer 2 is preferably composed of a monolayer. The carbon-containing layer 2 may include, for example, at least one selected from the group consisting of graphene and graphene oxide, may be composed of at least one selected from the group consisting of graphene and graphene oxide, or may be composed of graphene or graphene oxide.

[0034] Graphene is a sheet-like compound in which a hexagonal lattice structure composed of a plurality of carbon atoms is connected. Graphene is not particularly limited, but examples thereof include graphite in which a plurality of graphene sheets are stacked, cylindrical carbon nanotubes composed of one or a plurality of graphene sheets (e.g., single-walled carbon nanotubes (SWNH) and the like), and carbon nanohorns in which the tip of a carbon nanotube is closed and cone-shaped (e.g., single-walled carbon nanohorns (SWNH) and the like). From the viewpoint of facilitating the control of the opening 2a, the graphene etc. is preferably at least one selected from the group consisting of single-walled graphite, single-walled carbon nanotubes, and single-walled carbon nanohorns. Graphene oxide is a compound in which various oxygen-containing functional groups such as epoxy groups, carboxyl groups, carbonyl groups, and hydroxyl groups are introduced into graphene, and can also be called graphene having the oxygen-containing functional groups.

[0035] The thickness of the monolayer of graphene is generally 0.2 to 0.3 nm. The diameter of the carbon nanotube may be, for example, 0.5 to 40 nm, 0.4 to 1.0 nm, or 0.6 to 5.0 nm. The length of the carbon nanotube may be, for example, 10 to 5,000,000 nm, 20 to 20,000 nm, or 100 to 1,000,000 nm. The diameter of the carbon nanohorn may be, for example, 2 to 5 nm, 1 to 3 nm, or 2 to 4 nm. The length of the carbon nanohorn may be, for example, 40 to 50 nm, 20 to 40 nm, or 30 to 60 nm. The thickness of the monolayer of graphene, the diameter and length of the carbon nanotube, and the diameter and length of the carbon nanohorn refer to values ​​measured by an electron microscope.

[0036] The diameter of the opening 2a in the carbon-containing layer 2 can be adjusted appropriately depending on the use of the carbon material. The upper limit of the diameter of the opening 2a in the carbon-containing layer 2 may be, for example, less than 5 nm, less than 3 nm, less than 2 nm, or less than 1 nm. The lower limit of the diameter of the opening 2a in the carbon-containing layer 2 may be, for example, more than 0.3 nm, more than 0.5 nm, or more than 0.7 nm. The diameter of the opening 2a in the carbon-containing layer 2 may be adjusted within the above-mentioned range, and may be, for example, more than 0.7 nm and less than 2 nm. The diameter of the opening 2a in the carbon-containing layer 2 can be controlled, for example, by adjusting the conditions of the oxidation treatment of the carbon-containing layer (for example, heating temperature, heating time, etc.). The diameter of the opening 2a in the carbon-containing layer 2 can also be more easily adjusted by performing an oxidation treatment on the carbon-containing layer at a relatively low temperature of 280° C. or less and in a vacuum environment using ammonium nitrate. The openings 2a are regions (which may be called defects) where no elements constituting the carbon-containing layer 2 are present, and may be defects where some of the carbon atoms constituting the monolayer are removed, for example, when the carbon-containing layer 2 is a monolayer of graphene. In the defects, protons (-H), oxygen atoms (=O), hydroxyl groups (-OH), and the like are usually introduced in place of the removed carbon atoms.

[0037] The solid material 4 may be, for example, a compound having a planar structure, a π-conjugated macrocyclic compound having a planar structure, or a π-conjugated macrocyclic heterocyclic compound having a planar structure. For example, the carbon material 10 of the present disclosure may include a carbon-containing layer 2 (e.g., single-layer graphite, single-layer carbon nanotube, single-layer carbon nanohorn, etc.) having an opening 2a, and a π-conjugated macrocyclic compound provided so as to cover the opening 2a of the carbon-containing layer 2, and the π-conjugated macrocyclic compound may be arranged on the opening 2a so that the voids in the molecule of the π-conjugated macrocyclic compound are arranged. The carbon material 10 includes the solid material 4, which suppresses the spread of the opening 2a of the carbon-containing layer 2, and has a mechanical strength superior to that of a carbon-containing layer having an opening not including the solid material 4 (e.g., a conventional graphene sheet having holes).

[0038] Specifically, the solid material 4 may contain at least one selected from the group consisting of phthalocyanine, porphine, porphyrin, corrole, chlorine, and derivatives thereof, and may be at least one selected from the group consisting of phthalocyanine, porphine, porphyrin, corrole, chlorine, and derivatives thereof. The fact that the solid material 4 contains the compound can be confirmed by ultraviolet-visible absorption spectroscopy, and more specifically, it can be confirmed by measuring a peak in the Soret band (Soret band: a region corresponding to a wavelength around 400 nm). In addition, the phthalocyanine etc. in a free state exhibits strong absorption in the Q band (Q band: a region corresponding to a wavelength of 600 to 900 nm) in the ultraviolet-visible absorption spectrum, but by bonding to the carbon-containing layer 2 (for example, graphene, etc.), the absorption in the Q band is reduced, making it difficult to detect by inspection using the Q band.

[0039] Examples of the phthalocyanine derivative include a compound represented by the following general formula (1), naphthalocyanine, anthracocyanine, azulenocyanine, etc. From the viewpoint of further improving the strength of the bond with the carbon-containing layer 2 (e.g., bond by π-stack, etc.), the phthalocyanine derivative is preferably a compound represented by the following general formula (1).

[0040] [ka]

[0041] In general formula (1), there are multiple R 1 may be the same or different. In the general formula (1), R 1 R may be, for example, an alkyl group, an alkoxy group, a polyoxyalkylene group, and the like. 1 R may be linear, branched, or cyclic, but is preferably linear. 1 The number of carbon atoms constituting R may be adjusted according to the distance between the openings 2a in the carbon-containing layer 2. 1The number of carbon atoms constituting R may be, for example, 5 to 12, 6 to 10, or 7 to 9. 1 When the compound represented by general formula (1) contains a linear alkyl group having 5 to 12 carbon atoms, a linear alkoxy group having 5 to 12 carbon atoms, or a linear polyoxyalkylene group having 5 to 12 carbon atoms, the compound represented by general formula (1) can form a discotic liquid crystal, and therefore can be more easily arranged with a certain regularity on the carbon-containing layer 2.

[0042] Specific examples of phthalocyanines include 2,3,9,10,16,17,23,24-Octakis(octyloxy)-29H,31H-phthalocyanine and the like.

[0043] An example of the porphyrin derivative is a compound represented by the following general formula (2).

[0044] [ka]

[0045] In general formula (2), there are multiple R 2 may be the same or different. In the general formula (2), R 2 R may be, for example, an alkyl group, an alkoxy group, a polyoxyalkylene group, and the like. 2 R may be linear, branched, or cyclic, but is preferably linear. 2 The number of carbon atoms constituting R may be adjusted according to the distance between the openings 2a in the carbon-containing layer 2. 2 The number of carbon atoms constituting R may be, for example, 5 to 12, 6 to 10, or 7 to 9. 2 When the compound represented by general formula (2) contains a linear alkyl group having 5 to 12 carbon atoms, a linear alkoxy group having 5 to 12 carbon atoms, or a linear polyoxyalkylene group having 5 to 12 carbon atoms, the compound represented by general formula (2) can form a discotic liquid crystal, and therefore can be more easily arranged with a certain regularity on the carbon-containing layer 2.

[0046] Examples of the corrole derivative include compounds represented by the following general formula (3).

[0047] [ka]

[0048] In general formula (3), there are multiple R 3 may be the same or different. In the general formula (3), R 3 R may be, for example, an alkyl group, an alkoxy group, a polyoxyalkylene group, and the like. 3 R may be linear, branched, or cyclic, but is preferably linear. 3 The number of carbon atoms constituting R may be adjusted according to the distance between the openings 2a in the carbon-containing layer 2. 3 The number of carbon atoms constituting R may be, for example, 5 to 12, 6 to 10, or 7 to 9. 3 When the compound represented by general formula (3) contains a linear alkyl group having 5 to 12 carbon atoms, a linear alkoxy group having 5 to 12 carbon atoms, or a linear polyoxyalkylene group having 5 to 12 carbon atoms, the compound represented by general formula (3) can form a discotic liquid crystal, and therefore can be more easily arranged with a certain regularity on the carbon-containing layer 2.

[0049] An example of the chlorin derivative is a compound represented by the following general formula (4).

[0050] [ka]

[0051] In general formula (4), there are multiple R 4 may be the same or different. In the general formula (4), R 4 R may be, for example, an alkyl group, an alkoxy group, a polyoxyalkylene group, and the like. 4 R may be linear, branched, or cyclic, but is preferably linear. 4The number of carbon atoms constituting R may be adjusted according to the distance between the openings 2a in the carbon-containing layer 2. 4 The number of carbon atoms constituting R may be, for example, 5 to 12, 6 to 10, or 7 to 9. 4 When the compound represented by general formula (4) contains a linear alkyl group having 5 to 12 carbon atoms, a linear alkoxy group having 5 to 12 carbon atoms, or a linear polyoxyalkylene group having 5 to 12 carbon atoms, the compound represented by general formula (4) can form a discotic liquid crystal, and therefore can be more easily arranged with a certain regularity on the carbon-containing layer 2.

[0052] The pores 4a of the solid material 4 refer to regions where no elements constituting the solid material 4 exist. The pores 4a of the solid material 4 are usually located above the openings 2a of the carbon-containing layer 2. When the solid material 4 is, for example, at least one selected from the group consisting of phthalocyanine, porphine, porphyrin, corrole, chlorine, and derivatives thereof, the pores 4a may be regions surrounded by four pyrrole rings and methylene groups in phthalocyanine, porphine, porphyrin, corrole, chlorine, and derivatives thereof (regions where metal atoms are located when constituting a metal complex). A part of the solid materials 4 included in the carbon material 10 may have metal atoms in the pores 4a. Examples of metal atoms include transition metals, alkaline earth metals, and aluminum.

[0053] When the carbon-containing layer 2 contains at least one selected from the group consisting of graphene and graphene oxide, the solid material 4 contains a compound having a π-conjugated system, whereby bonding between the carbon-containing layer 2 and the solid material 4 (for example, bonding by π-stacking) is facilitated.

[0054] The carbon material 10 has an excellent specific surface area because the carbon-containing layer 2 has openings 2a. When the carbon material 10 is in a film form (for example, the carbon-containing layer 2 is graphene or the like), the specific surface area may be in the following range. That is, the specific surface area of ​​the carbon material 10 is, for example, 2000 m 2 / g or more, or 2500m 2The specific surface area of ​​the carbon material 10 can be, for example, 2800 m 2 / g or less, or 2600m 2 / g or less. When the carbon material 10 is cylindrical (for example, the carbon-containing layer 2 is a carbon nanotube or a carbon nanohorn, etc.), the specific surface area of ​​the carbon material 10 may be in the following range. The lower limit of the specific surface area of ​​the carbon material 10 is, for example, 300 m 2 / g or more, 500m 2 / g or more, 700m 2 / g or more, 800m 2 / g or more, 1000m 2 / g or more, 1200m 2 / g or more, or 1400m 2 The upper limit of the specific surface area of ​​the carbon material 10 can be, for example, 1600 m 2 / g or less, or 1500m 2 / g or less. When the lower limit of the specific surface area of ​​the carbon material 10 is within the above range, the decrease in mechanical strength can be more sufficiently suppressed. The specific surface area of ​​the carbon material 10 may be adjusted within the above range, for example, 300 to 1600 m 2 / g, or 600~1500m 2 / g.

[0055] The specific surface area in this specification is measured by the comparative plot method (particularly, α S -plot). More specifically, the surface area is determined by comparing the nitrogen adsorption isotherm measured at a temperature of 77K with the adsorption isotherm obtained for a standard sample with a known specific surface area. In the case of carbon materials, non-porous carbon is used as the standard sample. In this specification, the specific surface area is measured using non-porous carbon manufactured by Mitsubishi Chemical. The nitrogen adsorption isotherm is measured using an adsorption measuring device (manufactured by Quantachrome, product name: Autosorb-iQ). Prior to measurement, the measurement sample is treated for 2 hours at a pressure of 1 mPa or less and a temperature of 150°C using a pretreatment mechanism possessed by the adsorption measuring device. α S The plot shows the amount of nitrogen adsorption for the standard sample at a relative pressure of 0.4, S = 1, and normalized α SThe specific surface area is calculated by plotting the amount of adsorption against the slope of the αs-plot of the sample being measured as S(sample) and the α of the standard sample as S The slope of the plot is S (standard sample) and the surface area of ​​the standard sample is A (standard sample), and the value is calculated using the following formula. Specific surface area = S (sample) ÷ S (standard sample) × A (standard sample) The specific surface area is generally determined by the BET method. However, in the case of porous bodies with nanometer-level pore diameters such as carbon nanotubes, the BET method tends to overestimate the surface area. Therefore, in this specification, the above-mentioned comparative plot method is used as a method for determining the specific surface area more accurately.

[0056] By using the comparative plot method, the pore volume can be calculated. S -The slope of the linear region of the plot is α S Areas with small values ​​of and α S If the area where the value of α is large is different from the area where the value of α is large, it means that the sample has pores. S From the slope in the region where the value of α is small, the value of the specific surface area of ​​the sample can be obtained from the above formula, and α S The slope of the region with a large value of α gives the value of the external surface area of ​​the sample. S Straight lines and α in the region with large values ​​of S The intersection of the plot with the Y axis (which indicates the amount of adsorption), i.e., the Y-intercept value, is interpreted as the amount of molecules adsorbed inside the pores. If the Y-intercept value is W (pore adsorption), in the case of nitrogen adsorption measurement at 77K, the pore volume is calculated by the following formula. Pore ​​volume = W (amount of adsorption) ÷ (density of liquid nitrogen) Here, the density of liquid nitrogen is calculated using a value of 0.808 g / mL.

[0057] The carbon material 10 can be manufactured, for example, by the following method. One embodiment of the method for manufacturing the carbon material includes a first step of reducing the content of the solvent from a dispersion containing a carbon-containing layer, a metal complex, and a solvent to form a composite in which the metal complex is attached to the surface of the carbon-containing layer, a second step of heat-treating the composite to provide openings in the carbon-containing layer near metal atoms constituting the metal complex, and a third step of removing at least a portion of the metal atoms constituting the metal complex to form a solid having holes communicating with the openings.

[0058] The first step is a step of dispersing the carbon-containing layer and the metal complex in a solvent, and attaching the metal complex to the surface of the carbon-containing layer by utilizing the intermolecular force between the carbon-containing layer and the metal complex during the process of reducing the content of the solvent. In this step, an oxidation reaction proceeds in a later step in the part of the carbon-containing layer where the metal complex is attached, more specifically, in the region located in the vicinity of the metal atom constituting the metal complex. That is, this step can control the position where the opening is provided in the carbon-containing layer.

[0059] The carbon-containing layer may be, for example, a monolayer or a plurality of layers. The carbon-containing layer may preferably be a monolayer. The carbon-containing layer may, for example, include at least one selected from the group consisting of graphene and graphene oxide, or may be made of at least one selected from the group consisting of graphene and graphene oxide. The carbon-containing layer may be made of graphene or graphene oxide.

[0060] The metal complex may include a compound in which a metal atom is coordinated to the compound constituting the solid material 4. The metal complex may include, for example, a complex of a metal atom and at least one selected from phthalocyanine, porphin, porphyrin, corrole, chlorine, and derivatives thereof. That is, the metal complex may include, for example, at least one selected from the group consisting of a metal phthalocyanine compound, a metal porphin compound, a metal porphyrin compound, a metal corrole compound, a metal chlorine compound, and derivatives thereof, or may be at least one selected from the group consisting of a metal phthalocyanine compound, a metal porphin compound, a metal porphyrin compound, a metal corrole compound, a metal chlorine compound, and derivatives thereof.

[0061] By selecting a metal complex, the distance between the openings provided in the carbon-containing layer can be adjusted. For example, when a metal complex composed of a phthalocyanine derivative and a metal atom is used, the distance between the openings formed tends to increase in the order of phthalocyanine, naphthalocyanine, and anthracocyanine. In addition, when a compound represented by the above general formula (1) is adopted as a phthalocyanine derivative and a metal complex composed of the compound and a metal atom is used, the distance between the openings formed in the carbon-containing layer tends to increase in the order of phthalocyanine, naphthalocyanine, and anthracocyanine. 1 The greater the number of carbon atoms constituting R, the greater the distance between the openings that are formed. 1 By selecting the above, it becomes easier to control the order of arrangement between the metal complexes, and openings can be regularly formed in the carbon-containing layer. Although the reason why such an effect is obtained is not necessarily clear, the present inventors speculate that it is because the compound represented by the general formula (1) is a compound capable of forming a discotic liquid crystal phase, and contributes to controlling the mutual positions.

[0062] The metal atom constituting the metal complex is, for example, an element that promotes the oxidation reaction of the carbon-containing layer in a later step. The metal atom constituting the metal complex may, for example, include at least one selected from the group consisting of transition metals, alkaline earth metals, and aluminum, may be at least one selected from the group consisting of transition metals, alkaline earth metals, and aluminum, may be at least one selected from the group consisting of transition metals and alkaline earth metals, or may be at least one selected from the group consisting of transition metals. When the metal complex contains at least one selected from the above-mentioned metal atoms, it becomes easier to provide an opening in the carbon-containing layer. The transition metal may be, for example, titanium, vanadium, chromium, manganese, iron, cobalt, nickel, copper, zinc, etc., and may be vanadium, iron, cobalt, nickel, copper, and zinc, etc. The alkaline earth metal may be, for example, magnesium, strontium, and barium, etc. The lanthanoid may be, for example, lanthanum, cerium, etc.

[0063] Specific examples of metal complexes include Copper(II) 2,3,9,10,16,17,23,24-Octakis(octyloxy)-29H,31H-phthalocyanine and the like.

[0064] The solvent may be a compound capable of dispersing the carbon-containing layer and the metal complex, and may be, for example, an organic solvent such as toluene, benzene, xylene, or normal hexane.

[0065] The method for preparing the dispersion is not particularly limited, and may be adjusted, for example, by ultrasonic treatment. When preparing the dispersion, for example, the carbon-containing layer and the metal complex may be blended in a solvent and dispersed, or the carbon-containing layer and the metal complex may be separately dispersed in the dispersion and then mixed. The lower limit of the dispersion time (for example, the ultrasonic treatment time) for preparing the dispersion may be 10 hours or more, 15 hours or more, or 24 hours or more. The upper limit of the dispersion time for preparing the dispersion may be, for example, 50 hours or less, or 30 hours or less. The temperature for preparing the dispersion may be controlled. The upper limit of the temperature for preparing the dispersion may be, for example, 40°C or less, 30°C or less, or 25°C or less. The lower limit of the temperature for preparing the dispersion may be, for example, 15°C or more, or 20°C or more.

[0066] In the dispersion, the lower limit of the content of the metal complex may be, for example, 5 parts by mass or more, 10 parts by mass or more, 15 parts by mass or more, or 20 parts by mass or more, relative to 100 parts by mass of the carbon-containing layer. The upper limit of the content of the metal complex may be, for example, 40 parts by mass or less, 50 parts by mass or less, 60 parts by mass or less, or 65 parts by mass or less, relative to 100 parts by mass of the carbon-containing layer. The content of the metal complex may be adjusted within the above-mentioned range, and may be, for example, 5 to 40 parts by mass, 10 to 50 parts by mass, or 20 to 60 parts by mass, relative to 100 parts by mass of the carbon-containing layer.

[0067] The method for reducing the content of the solvent in the dispersion is not particularly limited, and examples thereof include heat treatment. The temperature of the heat treatment is desirably 80° C. or less, and may be, for example, 30 to 80° C., 40 to 80° C., or 50 to 80° C. By setting the temperature of the heat treatment to 80° C. or less, it is possible to further suppress the arrangement of the metal complexes attached to the carbon-containing layer from being broken. By setting the temperature of the heat treatment to 30° C. or more, it is possible to more easily reduce the content of the solvent, and therefore to more easily attach the metal complexes to the carbon-containing layer. More specifically, when carbon nanotubes and carbon nanohorns are used as the carbon-containing layer, the method may be such that the dispersion is first filtered through a membrane filter, and the collected matter is left in an oven set at a temperature of 30 to 80° C. and heat-treated. When graphene is used as the carbon-containing layer, the method may be such that the solid matter in the dispersion is first removed and heat-treated at a temperature of 40 to 80° C. on a hot plate. The reduction of the solvent content may be carried out over a predetermined period of time, for example, 10 minutes or more, 120 minutes or more, 360 minutes or more, or 720 minutes or more. The reduction of the solvent content may be carried out, for example, for 800 minutes or less. The reduction of the solvent content may be carried out within the above-mentioned treatment time, for example, for about 30 minutes.

[0068] The carbon-containing layer may be provided on a substrate of metal foil (e.g., copper foil, etc.). That is, the above-mentioned dispersion liquid may be brought into contact with the substrate by coating or the like to form a liquid film of the dispersion liquid, and then the content of the solvent in the liquid film may be reduced to provide the carbon-containing layer. By using a substrate, the handleability of the carbon-containing layer in the manufacturing process can be improved. In addition, a sheet made of a carbon material is formed by arranging the carbon-containing layers on the substrate, but if a metal complex is not used, this sheet usually has defects. For example, the sheet may have cuts, cracks, etc. However, by using a metal complex, the metal complex is coordinated in the gaps formed by the carbon-containing layers, and the occurrence of the above-mentioned defects can be reduced.

[0069] The second step is a step of heat treating the composite, which is the carbon-containing layer having the metal complex attached to the surface, to form openings in the carbon-containing layer by an oxidation reaction in the vicinity of the metal atoms.

[0070] The lower limit of the heating temperature in the second step may be, for example, 200°C or more, 250°C or more, or 300°C or more. By setting the lower limit of the heating temperature within the above range, the formation of openings in the carbon-containing layer becomes easier. The upper limit of the heating temperature in the second step may be, for example, 450°C or less, 430°C or less, or 400°C or less. By setting the upper limit of the heating temperature in the second step within the above range, the openings can be more effectively prevented from widening too much, and the formation of openings due to combustion at positions where no metal atoms are present can be more effectively prevented. The heating temperature in the second step may be adjusted within the above range, and may be, for example, 200 to 450°C, 250 to 430°C, or 250 to 400°C.

[0071] The time of the heat treatment in the second step can be adjusted according to the heating temperature, etc. For example, when the heat treatment is performed at a relatively high temperature, the heating time can be shortened, and even when the heat treatment is performed at a relatively low temperature, an opening can be formed by taking a sufficient heating time. The lower limit of the heat treatment time in the second step may be, for example, 5 minutes or more, 10 minutes or more, or 30 minutes or more. The lower limit of the heat treatment time in the second step may be, for example, 24 hours or less, 20 hours or less, 15 hours or less, or 10 hours or less. In this specification, the heating time means the time (retention time) during which the environmental temperature around the heat treatment object is maintained at a predetermined temperature after the temperature reaches the predetermined temperature.

[0072] The second step may be a step of heat-treating the composite in air, but is preferably a step of heat-treating the composite in an atmosphere containing oxygen. The oxygen-containing atmosphere (mixed gas atmosphere) may contain, in addition to oxygen, for example, nitrogen. The mixed gas preferably contains oxygen and nitrogen. The lower limit of the oxygen content in the mixed gas atmosphere may be 15 volume% or more, 20 volume% or more, or 25 volume% or more, based on the total amount of the mixed gas. The upper limit of the oxygen content in the mixed gas atmosphere may be 50 volume% or less, 40 volume% or less, or 30 volume% or less, based on the total amount of the mixed gas.

[0073] The second step may be a step performed under vacuum. In this case, ammonium nitrate can be used as an oxygen source. By using ammonium nitrate, it is possible to lower the heat treatment temperature, which makes it easier to control the reaction system. Specifically, the above-mentioned complex is made to coexist with ammonium nitrate and heat-treated at 200 to 280°C under vacuum, whereby ammonium nitrate can be decomposed and oxygen can be generated. The oxygen and the metal element in the complex are present, so that an opening can be provided in the carbon-containing layer near the metal atom constituting the metal complex.

[0074] The third step is a step of providing openings in the carbon-containing layer and then removing at least a portion of the metal atoms from the metal complex to provide a solid having pores communicating with the openings.

[0075] The method for removing the metal atoms in the third step is not particularly limited, and may be, for example, performed by acid treatment. That is, the third step may be a step of removing at least a part of the metal atoms by acid treatment. By performing the third step by acid treatment, the removal of the metal atoms and the formation of the holes are made easier.

[0076] The above-mentioned method for producing a carbon material may have other steps in addition to the first step, the second step, and the third step. The other steps may include, for example, a step of providing a support film on the carbon-containing layer, a step of removing the base material, a step of providing water permeable holes in the support film, and the like. The support film may be made of, for example, a photoresist, and may be a negative photoresist. By making the support film of a photoresist, water permeable holes can be more easily formed in a later step.

[0077] Another embodiment of the method for producing a carbon material includes, instead of the first step described above, a step of forming a composite to which a metal complex is attached by depositing the metal complex on a carbon-containing layer containing graphene. The other steps may be the same as those of the production method described above. The deposition in this embodiment may be performed, for example, by a cluster ion beam deposition method. Conditions for this may include adjusting the ionizing electron voltage, ion beam current, and degree of vacuum. The ionizing electron voltage may be, for example, 300 V or more. The ion beam current may be, for example, 300 mA or more. The degree of vacuum may be, for example, 1×10 -2 The method according to the present embodiment can produce a carbon material without using a solvent, and therefore can produce a carbon material more simply than the above-described production method.

[0078] In addition, in yet another embodiment of the method for producing a carbon material, instead of the first step described above, a step of spreading a dispersion containing a metal complex and a solvent on water (e.g., ultrapure water, etc.) to form a liquid film made of the dispersion, reducing the content of the solvent in the liquid film to form a molecular layer containing the metal complex, and scooping the molecular layer onto a carbon-containing layer containing graphene to form a complex to which the metal complex is attached. The other steps may be the same as those of the production method described above. The step in this embodiment can also be said to be a step of forming a carbon material composed of a metal complex on a carbon-containing layer containing graphene by the Langmuir-Blodgett method. According to the method of this embodiment, a carbon material in which a metal complex is more uniformly arranged on a carbon-containing layer can be produced compared to other production methods.

[0079] Although several embodiments have been described above, the present disclosure is not limited to the above-described embodiments. In addition, the descriptions of the above-described embodiments can be mutually applied. EXAMPLES

[0080] The present disclosure will be described in more detail below with reference to examples and comparative examples. However, the present disclosure is not limited to the following examples.

[0081] Example 1 1 mg of single-walled carbon nanohorn and 5 mL of toluene were weighed out and placed in a container, and dispersed using an ultrasonic cleaner for 15 minutes at 25° C. to prepare a single-walled carbon nanohorn dispersion A. Next, 0.5 mg of copper phthalocyanine (Copper(II) 2,3,9,10,16,17,23,24-Octakis(octyloxy)-29H,31H-phthalocyanine) and 10 mL of toluene were weighed out and placed in a container, and dispersed using an ultrasonic cleaner for 15 minutes at 25° C. to prepare a copper phthalocyanine dispersion B.

[0082] The entire amount of the dispersion A and the dispersion B prepared as described above were mixed, and the mixture was dispersed for 24 hours at 25°C using an ultrasonic cleaner to prepare dispersion C. After the dispersion treatment, dispersion C was filtered through a membrane filter to obtain a single-layer carbon nanohorn carrying copper phthalocyanine (corresponding to a carbon-containing layer to which a metal complex is attached) as a collected product. The single-layer carbon nanohorn carrying copper phthalocyanine obtained was dried for 2 hours at 80°C. The amount of copper phthalocyanine in the filtrate filtered through the membrane filter was quantified using an ultraviolet-visible spectrometer, and the difference from the initial amount was calculated. The amount of copper phthalocyanine carried on the single-layer carbon nanohorn was determined on the assumption that this difference was carried on the single-layer carbon nanohorn. The amount of copper phthalocyanine carried on the single-layer carbon nanohorn was 1% by mass.

[0083] After drying, the single-walled carbon nanohorn carrying copper phthalocyanine was placed in a heating furnace and heat-treated for 1 hour under conditions of 300°C (573K) and a gas flow of 100mL / min of oxygen and nitrogen mixed gas (a mixed gas of oxygen and nitrogen in a volume ratio of 20% by volume:80% by volume), to prepare a perforated carbon nanohorn. This was used as the carbon material of Example 1. The heating rate was 1°C / min, and cooling was natural.

[0084] Example 2 A perforated carbon nanohorn was prepared in the same manner as in Example 1, except that the amount of copper phthalocyanine supported on the single-walled carbon nanohorn was 10 mass %.

[0085] Comparative Example 1 Dispersion A prepared in Example 1 was filtered through a membrane filter, and the single-walled carbon nanohorn obtained as the filter cake was dried at 80°C for 2 hours to obtain the single-walled carbon nanohorn, which was used as the carbon material of Comparative Example 1.

[0086] Comparative Example 2 The single-walled carbon nanohorn obtained in Comparative Example 1 was placed in a heating furnace and heat-treated for 1 hour under conditions of 300°C (573K) and a 100mL / min airflow of a mixed gas of oxygen and nitrogen (a mixed gas of oxygen and nitrogen in a volume ratio of 20% by volume:80% by volume), to prepare a perforated carbon nanohorn. This was used as the carbon material of Comparative Example 2. The heating rate was 1°C / min, and cooling was natural.

[0087] <Evaluation of carbon materials: Measurement of ultraviolet and visible absorption spectra> The ultraviolet-visible absorption spectrum was measured for each of the carbon materials prepared in Example 1 and Example 2. The results are shown in Figures 2 and 3.

[0088] FIG. 2 is a graph showing the ultraviolet-visible absorption spectrum of the carbon material prepared in Example 1. FIG. 3 is a graph showing the ultraviolet-visible absorption spectrum of the carbon material prepared in Example 2. For comparison, FIG. 2 and FIG. 3 also show the ultraviolet-visible absorption spectrum of the copper phthalocyanine used in the preparation of the carbon material. In the ultraviolet-visible absorption spectrum shown in FIG. 2 and FIG. 3, a peak derived from the phthalocyanine skeleton, which does not exist in the single-walled carbon nanohorn, was confirmed in the Soret band. In addition, it was confirmed that the ultraviolet-visible absorption spectrum does not have a peak in the Q band derived from the phthalocyanine skeleton. From this result, it was confirmed that the copper phthalocyanine and the single-walled carbon nanohorn are not simply mixed, but that the copper phthalocyanine is supported on the single-walled carbon nanohorn.

[0089] <Evaluation of carbon materials: Thermogravimetry> Thermogravimetric measurements were carried out on the carbon materials prepared in Examples 1 and 2. The results are shown in Figures 4 and 5.

[0090] Specifically, thermogravimetry was performed using a simultaneous differential thermal and thermogravimetry analyzer (manufactured by Hitachi High-Technologies Corporation, product name: STA7200). The heating rate was 1 K / min. In addition, in the measurement under an oxygen atmosphere, air was used and the flow rate was adjusted to 100 mL / min. In addition, in the measurement under a nitrogen atmosphere, pure nitrogen was used and the flow rate was adjusted to 100 mL / min.

[0091] FIG. 4 is a graph showing the results of thermogravimetry of the carbon material under an oxygen atmosphere. FIG. 5 is a graph showing the results of thermogravimetry of the carbon material under a nitrogen atmosphere. In FIG. 4, for comparison, the results of the above-mentioned thermogravimetry of the copper phthalocyanine used in the preparation of the carbon material and the single-walled carbon nanohorn prepared in Comparative Example 1 are also shown. From the graph shown in FIG. 2, it can be confirmed that the weight loss start temperature decreases as the amount of copper phthalocyanine supported increases, based on the weight loss temperature of the single-walled carbon nanohorn not supported with copper phthalocyanine. From this result, it was confirmed that the support of copper phthalocyanine can reduce the start temperature of perforation of the single-walled carbon nanohorn. In other words, it was confirmed that by supporting copper phthalocyanine, perforation can be performed under milder conditions, and the formation of openings can be more easily controlled. In addition, from the graph shown in FIG. 5, it was confirmed that the single-walled carbon nanohorn exists stably under nitrogen, and the weight loss is slight. From this result, it was confirmed that the weight loss shown in FIG. 4 was caused by the oxidation reaction of the single-walled carbon nanohorns mediated by oxygen.

[0092] <Evaluation of carbon materials: Measurement of nitrogen adsorption amount> The nitrogen adsorption amount was measured for each of the carbon materials prepared in Example 1, Example 2, Comparative Example 1, and Comparative Example 2 using a fully automatic gas adsorption amount measuring device (manufactured by Anton Paar Japan, product name: Autosorb-iQ). The results are shown in FIG.

[0093] Specifically, the carbon material sample was first pretreated using an adsorption measurement device (manufactured by Quantachrome, product name: Autosorb-iQ). For pretreatment, a degassing treatment was performed for 2 hours at a temperature of 150°C under a vacuum of 1 mPa or less using a pretreatment device included in the adsorption measurement device. The sample was then transferred to the measurement section, and the amount of nitrogen adsorption was measured at a temperature of 77K using liquid nitrogen as a refrigerant.

[0094] Fig. 6 is a graph showing the relationship between the amount of nitrogen adsorption of the carbon material and the relative pressure of nitrogen. In Fig. 6, the adsorption result of the carbon material prepared in Example 1 is shown as "1%Pc / ox-SWCNH_573K", the adsorption result of the carbon material prepared in Example 2 is shown as "10%Pc / ox-SWCNH_573K", the adsorption result of the single-walled carbon nanohorn prepared in Comparative Example 1 is shown as "Prisine SWCNH", and the adsorption result of the carbon material prepared in Comparative Example 2 is shown as "ox-SWCNH_537K". In addition, the nitrogen desorption results for each carbon material are shown with an outlined symbol.

[0095] 6, in Example 1, Example 2, and Comparative Example 2, where heat treatment was performed, the amount of nitrogen adsorption was large even at a low relative pressure (P / P0) stage, compared to the results of Comparative Example 1. From this result, it was confirmed that the single-walled carbon nanohorns obtained in Example 1, Example 2, and Comparative Example 2 had openings, and nitrogen penetrated into the carbon nanohorns, with the internal surfaces of the carbon nanohorns also contributing to adsorption.

[0096] <Evaluation of carbon materials: Measurement of gas adsorption amount> The size of the opening diameter formed in the carbon material was evaluated for each of the carbon materials prepared in Example 1, Example 2, Comparative Example 1, and Comparative Example 2. The evaluation was performed by measuring the gas adsorption amount using argon (Ar, molecular size: 0.335 nm), which is a molecule smaller than a nitrogen molecule (N2, molecular size: 0.363 nm), and sulfur hexafluoride gas (SF6, molecular size: 0.525 nm), which is a molecule larger than a nitrogen molecule, and converting the gas adsorption amount per pore volume using the value of the pore volume calculated using the measurement result of the nitrogen adsorption amount described above.

[0097] The argon adsorption amount and hydrogen hexafluoride adsorption amount were measured using the same adsorption measuring device (Quantachrome, product name: Autosorb-iQ) as in the nitrogen adsorption experiment described above. The pretreatment conditions were the same as those in the nitrogen adsorption experiment. The measurement was performed under the condition of immersing the cell in an ice-water thermostatic bath at a temperature of 273K.

[0098] The results are shown in Fig. 7 and Fig. 8. Fig. 7 is a graph showing the relationship between the argon adsorption amount per pore volume determined by nitrogen adsorption of the carbon material and the argon pressure. Fig. 8 is a graph showing the relationship between the sulfur hexafluoride adsorption amount per pore volume determined by nitrogen adsorption of the carbon material and the sulfur hexafluoride gas pressure. In Fig. 7 and Fig. 8, the adsorption result of the carbon material prepared in Example 1 is shown as "1%Pc / ox-SWCNH_573K", the adsorption result of the carbon material prepared in Example 2 is shown as "10%Pc / ox-SWCNH_573K", the adsorption result of the carbon material prepared in Comparative Example 1 is shown as "Prisine SWCNH", and the adsorption result of the carbon material prepared in Comparative Example 2 is shown as "ox-SWCNH_537K".

[0099] As shown in FIG. 7, the carbon materials of Examples 1 and 2 have slightly larger adsorption amounts than the carbon material of Comparative Example 2. This means that the carbon materials of Examples 1 and 2 have more holes than the carbon material prepared in Comparative Example 2. This can also be confirmed by comparing Examples 1 and 2, where the carbon material of Example 2, which uses a larger amount of metal complex, adsorbs more argon than the carbon material of Example 1. In addition, as shown in FIG. 8, the adsorption amount of sulfur hexafluoride in the single-walled carbon nanohorn of Comparative Example 2 is significantly larger than the adsorption amount of sulfur hexafluoride in the carbon materials of Examples 1 and 2. This means that the single-walled carbon nanohorn with openings of Comparative Example 2 has a large opening size, or cracks occur during the opening formation, causing the carbon nanohorn to tear. From the above results, it was confirmed that the technology disclosed herein can adjust the number of openings while controlling the opening diameter on the surface of the carbon material.

[0100] Example 3 A sample in which graphene (single layer) was grown on a 10 mm square copper foil (hereinafter referred to as graphene / copper foil, manufactured by Graphene Platform Co., Ltd.) was immersed in 10 mL of acetone, 10 mL of methanol, and 10 mL of ultrapure water, in that order, for 5 minutes each, for permeation cleaning, and then the sample was dried. Next, 0.5 mg of copper phthalocyanine (Copper (II) 2,3,9,10,16,17,23,24-Octakis(octyloxy)-29H,31H-phthalocyanine) and 10 mL of toluene were weighed out and dispersed in a container at 25°C for 15 minutes using an ultrasonic cleaner to prepare a copper phthalocyanine dispersion B2.

[0101] The washed and dried graphene / copper foil was immersed in dispersion B2 and treated at 65° C. for 1 hour to form a monolayer of copper phthalocyanine on the graphene side of the graphene / copper foil. The sheet was naturally cooled to a temperature of 40° C. or less, removed from dispersion B2, washed with normal hexane, and dried to obtain a sheet having a monolayer of copper phthalocyanine provided on the graphene side of the graphene / copper foil.

[0102] Next, the sheet was placed in a heating furnace and heated for 1 hour under a 100 mL / min airflow of a mixed gas of oxygen and nitrogen (a mixed gas of oxygen and nitrogen at a volume ratio of 20% by volume:80% by volume) at 300°C (573K) to perforate the graphite and form openings. This was the carbon material of Example 3. The heating rate was 1°C / min, and the material was cooled naturally.

[0103] Example 4 In the same manner as in Example 3, a sheet was obtained in which a monomolecular layer of copper phthalocyanine was provided on the graphene side of the graphene / copper foil.

[0104] On the surface of the sheet on which the copper phthalocyanine monolayer was formed, 100 μL of an ethanol solution with an ammonium nitrate concentration of 0.5 μmol / L was dropped, cast, and dried for 1 hour at 30° C. In this way, a sample was prepared in which ammonium nitrate was attached to the surface of the sheet on which the copper phthalocyanine monolayer was formed.

[0105] Next, the sample to which the ammonium nitrate was attached was placed in a heating furnace and formed into a 250 under vacuum. This was used as the carbon material of Example 4. The heating rate was 1° C. / min, and the cooling was natural.

[0106] For reference, electron microscope images of the sheet surface at each stage in the manufacturing process of the carbon material in Example 4 are shown in Fig. 9. (a) in Fig. 9 shows the surface of a sheet made of graphite obtained by casting on copper foil and drying, and (b) shows the surface of the sheet after heat treatment at 250°C.

[0107] Comparative Example 3 A carbon material was prepared in the same manner as in Example 4, except that copper phthalocyanine was not used. FIG. 10 shows an electron microscope image of a sheet surface in the manufacturing process of the carbon material in Comparative Example 3. FIG. 10 shows the surface of a sheet composed of graphite obtained by casting on copper foil and drying. It can be seen that macroscopic cracks are generated on the sheet because copper phthalocyanine was not used.

[0108] From the results shown in Fig. 10, it can be seen that defects such as cracks can occur during the preparation process of the sheet. And, as shown in Fig. 9(a), when copper phthalocyanine was used, it was confirmed that the copper phthalocyanine etc. was placed in the defective portion and filled the defect. And, as shown in Fig. 9(b), it was confirmed that the filling of the defect by the copper phthalocyanine etc. was maintained even after the graphite was heated and holes were formed in the surface of the graphite. [Industrial Applicability]

[0109] According to the present disclosure, it is possible to provide a carbon material having pores and excellent mechanical strength in which cracks are suppressed from spreading, etc. According to the present disclosure, it is also possible to provide a manufacturing method for manufacturing the above-mentioned carbon material. [Explanation of symbols]

[0110] 2...carbon-containing layer, 2a...opening, 4...solid matter, 4a...pore, 10...carbon material.

Claims

1. a carbon-containing layer having an opening; and a solid body provided so as to cover the opening of the carbon-containing layer; the solid body has a hole communicating with the opening, The carbon material, wherein the solid material contains at least one selected from the group consisting of phthalocyanine, porphine, porphyrin, corrole, chlorine, and derivatives thereof.

2. The carbon material of claim 1 , wherein the carbon-containing layer is a monolayer.

3. The carbon material according to claim 1 or 2, wherein the carbon-containing layer contains at least one selected from the group consisting of graphene and graphene oxide.

4. The carbon material according to any one of claims 1 to 3, wherein a plurality of the solids are arranged on the carbon-containing layer.

5. The carbon material according to any one of claims 1 to 4, wherein a plurality of the solids are regularly arranged on the carbon-containing layer.

6. a first step of reducing a content of the solvent from a dispersion containing a carbon-containing layer, a metal complex, and a solvent to form a composite in which the metal complex is attached to a surface of the carbon-containing layer; a second step of heat-treating the composite to provide openings in the carbon-containing layer near metal atoms constituting the metal complex; and a third step of removing at least a portion of the metal atoms constituting the metal complex to form a solid material having a hole communicating with the opening.

7. The method according to claim 6, wherein the heating temperature in the second step is 200 to 450°C.

8. The manufacturing method according to claim 6 or 7, wherein the second step is a step of causing the complex to coexist with ammonium nitrate and heat-treating it at 200 to 280° C. under vacuum to provide openings in the carbon-containing layer near metal atoms constituting the metal complex.

9. The method according to any one of claims 6 to 8, wherein the third step is a step of removing at least a part of the metal atoms by an acid treatment.

10. The method according to any one of claims 6 to 9, wherein the metal atom comprises at least one selected from the group consisting of transition metals, alkaline earth metals, and aluminum.

11. The method according to claim 10, wherein the transition metal comprises at least one metal atom selected from the group consisting of vanadium, iron, cobalt, nickel, copper, zinc, aluminum, alkaline earth metals, and lanthanoids.

12. The method according to any one of claims 6 to 11, wherein the carbon-containing layer is a monolayer.

13. The method according to any one of claims 6 to 12, wherein the carbon-containing layer contains at least one selected from the group consisting of graphene and graphene oxide.

14. The method according to any one of claims 6 to 13, wherein the metal complex comprises a complex of a metal atom and at least one selected from the group consisting of phthalocyanine, porphine, porphyrin, corrole, chlorine, and derivatives thereof.

15. The method according to any one of claims 6 to 14, wherein a plurality of the solid objects are arranged on the carbon-containing layer.

16. The method according to any one of claims 6 to 15, wherein a plurality of the solid objects are regularly arranged on the carbon-containing layer.

Citation Information

Patent Citations

  • Deionization or desalting by perforated graphene

    JP2013536077A

  • Method for producing modified-graphene-like carbon material, modified-graphene-like carbon material, and resin composite material

    JP2014076909A

  • Functionalization of graphene pores for deionization

    JP2015516286A

  • Photocatalyst structure, method for producing the same and photocatalyst-dispersed liquid

    JP2016163858A

  • ULTRA-THIN GRAPHEN-BASED MEMBRANES FOR WATER TREATMENT AND THEIR FORMATION AND USE

    JP2017500195A